Preferences for breeding places for Aedes spp. mosquitoes on materials and location of containers in the working area of Lateri Health Center, Ambon City - Robi Akollo (LPPM Universitas dr. Soebandi, 2024)
Background: The mosquitoes Aedes aegypti and Ae. albopictus is a vector of dengue fever in Indonesia. Container characteristics such as material, color, location, shape, volume and water origin influence female Aedes spp mosquitoes in choosing a place to lay their eggs. Mosquito Ae. aegypti prefers artificial containers as a breeding place, while the Ae. albopictus prefers natural containers. Mosquito Ae. aegypti prefers to be indoors while the Ae. albopictus outdoors. Purpose: knowing the preferences for breeding places for Ae mosquitoes. aegypti and Ae. albopictus on materials and location of containers in the Lateri Health Center Working Area, Ambon City. Methods: This research is a descriptive and analytical study with a cross sectional research design. Larvae collection was carried out in Lateri and Lata villages, Lateri Health Center Working Area. Habitat characterization of Ae. aegypti and Ae. albopictus is carried out visually including the location and material of the container. Identification of larvae using the Aedes genus identification key with a microscope. Results: The container materials found at the research location were artificial containers. The basic materials for the containers made in this research are cement, ceramic, plastic, glass, rubber and aluminum. Mosquito larvae Ae. aegypti are more commonly found inside homes while the mosquito larvae of Ae. albopictus is more commonly found outside the home. Conclusions: Mosquito Ae. aegypti and Ae. albopictus uses artificial containers as a breeding place. Mosquito larvae Ae. aegypti are more commonly found inside homes, while Ae. albopictus outdoors